Implementasi Program Kampus Mengajar Berbasis Literasi di SMKN 4 Palangka Raya - Putrawiyanta, I Putu; Saputra, Dikki; Silaban, Febry Samuel; Sinaga, Wilmar G. M; Ginting, Nia D.; Sitorus, Yosua F.; Yusandi, Yusandi (Universitas Negeri Gorontalo, 2026)
The Teaching Campus Program provides a collaborative space between university students and vocational high school students to improve the quality of context-based learning. This article aims to describe the implementation of the mining literacy program in improving the competency of students at SMK Negeri 4 Palangka Raya while supporting the achievement of the Sustainable Development Goals (SDGs). Six literacy programs were implemented by Mining Engineering students at Palangka Raya University. This program contributes to the achievement of SDGs 4 (Quality Education), SDGs 8 (Decent Work and Economic Growth), SDGs 12 (Responsible Consumption and Production), and SDGs 13 (Addressing Climate Change).